Labors Appropriate to Their Sex : Gender, Labor, and Politics in Urban Chile, 1900-1930 - Hutchison, Elizabeth Q. (Elizabeth Quay) (Book collections on Project MUSE., 2001)
The first systematic account of Chilean women's labor from 1885 to 1930 showing how women's paid labor became a locus of anxiety for a society confronting social problems linked to modernization.